Implementing the Personalised Learning Framework in University Studies: What Is It That Works? - Kontrimiene, Simona; Venslovaite, Vita; Alisauskiene, Stefanija; Kaminskiene, Lina; Rutkiene, Ausra; O’Mahony, Catherine; Lee, Laura; Guðjónsdóttir, Hafdís; Kristinsdóttir, Jónína V.; Wozniczka, Anna K. (Acta Paedagogica Vilnensia, 2021)
Personalised learning embraces the elements of mutual ownership by learners and teachers, flexible content, tools and learning environments, targeted support, and data-driven reflection and decision making. The current study utilises a mix of instrumental case study (Stake, 1995) and deductive thematic analysis (Braun, Clarke & Terry, 2015; Terry et al., 2017) methods to explore the accounts of students of two teacher education study programmes at Vilnius University. The programmes were innovated to include practices of personalised learning in line with the framework developed by partners of the Erasmus+ Strategic Partnership Project INTERPEARL (Innovative Teacher Education through Personalised Learning). The results yielded three major themes which capture the successes and setbacks the students face, namely, personalisation in vivo: facilitation of growth as a would-be teacher; personalisation not manifest: what does not work; and personalisation in the making: the dos and don’ts.